Analisis Indikator Rasio Angka Kematian di Ruang ICU/ICCU pada Rumah Sakit - Patricia Tio Gabriella Silaban; Eva Vanya Theresia Br Tarigan (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
Hospital statistics are health statistics based on medical record data as a producer of health information to obtain certainty for health practitioners, management and medical personnel in making decisions related to health services in hospitals. Health services in hospitals include services in the intensive unit, namely the ICU. Patient mortality is an indicator of the quality of nursing services in the ICU. The ability to serve emergency and critical patients affects the quality of service that contributes to mortality rates (Hanafie 2008). The purpose of this paper is to analyze the factors and patient mortality rates in the ICU room in the hospital. The method used for literature review is a method that is done by collecting, identifying, and analyzing research works that have been produced by researchers. The analysis was carried out by calculating the percentage of 4 ICUs in different hospitals that had been collected from the work of researchers. It is known that the mortality rate indicator in Icu and Hcu Rsup Dr. Kariadi has the highest rate of 49.5%, followed by the Intesive Care Unit (ICU) room of the second West Java regional hospital 29.9%, the Intensive Therapy room of Sanglah Central General Hospital Denpasar third 24.8% and which has the lowest mortality rate in the Icu / Hcu Room at Rsud Wajo Regency South Sulawesi 2.4%. The highest mortality rate indicator in Dr. Kariadi Hospital and the lowest mortality rate in the ICU of Wajo District Hospital, South Sulawesi.